Conscientiousness, Activity Engagement, and Momentary Affect in Oldest-Old Adulthood. (26th August 2020) - Windsor, Tim D; Curtis, Rachel G; Gerstorf, Denis; Hoppmann, Christiane A; Luszcz, Mary A
Abstract: Objectives: Remaining engaged with life is a hallmark of aging well and pursuing personally meaningful activities is presumably important for late-life affect. We examined how moment-to-moment variability in meaning and degree of challenge ascribed to daily activities relate to positive and negative affect in very old adults. Possible moderating effects of between-person differences in conscientiousness on meaning-affect associations were also examined. Methods: Participants were 73 adults aged 89 years on average from the Australian Daily Life Time-Sampling module of the Australian Longitudinal Study of Aging. Participants provided self-report data on activity engagement (meaning and challenge associated with activities) and affect, on 5 occasions per day for a period of 7 consecutive days. Results: Within-person associations of activity meaning with affect varied as a function of within-person challenge ratings. Specifically, gains in positive affect associated with meaningful activity were more strongly evident when activities were regarded as more challenging. In contrast, meaningful activity was associated with higher negative affect when activities were regarded as more challenging and lower negative affect when activities were regarded as less challenging. Conscientiousness did not moderate associations of activity meaning with affect. Discussion: Our findings shed light on the intricate interplay between maintaining meaningful engagement and daily emotional experiences in very old age. We discuss theoretical and practical implications and consider the role of late-life conscientiousness for self- and emotion regulation.